IMPLEMENTASI KURIKULUM MERDEKA: STIMULUS DALAM PEMBELAJARAN BAHASA ARAB - fatihati, zhafira; Nuril Mufidah; Nur Rahmad Yahya Wijaya (BARA AJI: Jurnal Keilmuan Bahasa Arab dan Pengajarannya, 2025)
Abstract Learning Arabic using the Discovery Learning model is focused on language learning, students are actively involved in receiving and searching for learning material. There are six stages in determining this method, namely: stimulation, problem statement/identification, data collection, data processing, verification, and generalization. This study aims to determine the implementation of the stimulus in learning Arabic. The research method used in this research is literature study through references starting from 2012 to 2023. There are three results obtained from this study, including: individual recognition of environment (perceptual response), reaction patterns (emotional response), and behavior (response behavior).